Serum-free alginate-C2C12 cells microcapsule as a model of alternative animal protein source - Scheffold, Jana; Bruheim, Per; Kjesbu, Joachim Sebastian; Jang, Mi (Frontiers in Nutrition, 2023)
Due to the climate change crisis, and environmental impacts of the traditional meat sector, the production of artificial animal protein based on in vitro cell culture technology is proposed as an alternative. Furthermore, since traditional animal serum-supplemented cultures pose scientific challenges such as batch variation and contamination risks, artificial animal protein cultures are currently in urgent need of not only serum-free cultures, but also microcarrier culture systems for scalability. However, serum-free microcarrier-based culture system for the differentiation of muscle cells is not available to date. Therefore, we established an edible alginate microcapsules culture system for the differentiation of C2C12 cells in serum-free conditions. Furthermore, metabolites related to central carbon metabolism were profiled based on targeted metabolomics using mass spectrometry. The C2C12 cells cultured in alginate microcapsules displayed high viability throughout 7 days and successfully differentiated within 4 days in serum and serum-free cultures except for AIM-V cultures, which was confirmed by CK activity and MHC immunostaining. Lastly, to the best of our knowledge, this is the first report to compare metabolite profiles between monolayer and alginate microcapsule culture systems. Alginate microcapsule culture showed higher levels of intracellular glycolysis and TCA cycle intermediates, lactate, and the contribution of essential amino acids compared to the monolayer culture. We believe our serum-free alginate microcapsule culture system is adaptable to different species of muscle cells and contributes to future food technology as a proof of concept for the scalability of alternative animal protein source production.